(NpOLIFONIQ STROGOGO STILQs (Nu^EBNOE POSOBIE DLQ spos - (Nn(B.(Nw(B.(NmART@[EWA(B.s ((NmOSKWAs (NsANKT(B-(NpETERBURGs, 2021)
(Nu^EBNOE POSOBIE QWLQETSQ KRATKIM IZLOVENIEM TEORETI^ESKOGO KURSA(B.s
Keywords: (NtEORIQ(B.s